Relationship between cytokine release and stress hyperglycemia in patients hospitalized with COVID-19 infection - Da Porto, Andrea; Tascini, Carlo; Colussi, Gianluca; Peghin, Maddalena; Graziano, Elena; De Carlo, Chiara; Bulfone, Luca; Antonello, Martina; Sozio, Emanuela; Fabris, Martina; Curcio, Francesco; Pucillo, Carlo; et al. (Frontiers in Medicine, 2022)
Abstract Stress hyperglycemia is a frequent finding in patients with COVID-19 infection and could affect the outcome of disease. Cytokines released in response to infection could have adverse effects on insulin sensitivity and pancreatic beta-cell function. The aim of the study was to examine the relationships of stress hyperglycemia with cytokines and clinical outcomes in hospitalized patients with COVID-19. Methods: In a cross-sectional analysis of 150 patients hospitalized for COVID-19 infection who were included in the GIRA-COVID database, we identified patients with stress hyperglycemia by calculation of the Stress Hyperglycemia Ratio (SHR) and use of a cut-off of 1.14. Plasma levels of cytokines principally involved in COVID-19 infection-related cytokine storm were measured. Outcome variables were use of mechanical ventilation and death within 60 days from hospital admission. Results: Patients with SHR>1.14 had significantly higher plasma insulin, HOMA-index, and levels of interleukin-10 (IL-10), interleukin-10/tumor necrosis factor-a ratio (IL-10/TNF-a), and CXC motif chemokine ligand 10 (CXCL10) than patients with SHR≤1.14. IL-10, IL-10/TNF-a ratio, CXCL10, and IFN-γ were significantly and directly related with SHR in univariate analysis and multivariate logistic regression models showed that IL-10, IL-10/TNF-a ratio, and CXCL10 were independently associated with SHR>1.14. In a multivariate logistic model, stress hyperglycemia predicted use of mechanical ventilation (OR 2.453; CI 1.078-6.012) and death (OR 2.281; CI 1.049-7.369) independently of diabetes and other major confounders. Conclusions: In patients hospitalized for COVID-19 infection, stress hyperglycemia is associated with worse clinical outcomes and is independently related to levels of cytokines that might impair glucose homeostasis.